Juridical Analysis of Supreme Court Decision No. 321 K/Pdt/2017: Implications of Name Borrowing Agreement for Land Ownership by Foreigners - Prayoga, Evandito Raihan; Prastyanti, Rina Arum (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines Supreme Court Decision No. 321 K/Pdt/2017 which deals with name borrowing agreements for land ownership by foreigners in Indonesia. In the context of increasing foreign investment, the practice of name borrowing is often a solution for foreigners to circumvent the prohibition on land ownership, but it also poses various legal challenges. Through a normative analytical descriptive juridical approach, this study analyzes the substance of the decision, the legal risks for the parties involved, and the social and economic implications of this practice. The results of the analysis show that name loan agreements are not legally recognized and are potentially null and void, resulting in legal uncertainty and conflicts that harm both foreigners and Indonesian citizens. The research also highlights that the absence of legal protection for the parties can result in financial and reputational losses. Overall, the findings indicate the need for policy reformulation and stricter regulations to govern land ownership by foreigners in Indonesia, in order to maintain social and economic balance and encourage sustainable investment development.